2014
DOI: 10.5888/pcd11.130234
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Khat and Concurrent Khat and Tobacco Use Are Associated With Subjective Sleep Quality

Abstract: IntroductionKhat (Catha edulis) is widely used in East Africa and the Middle East, often in combination with tobacco smoking. Sleep disturbance has been linked with habitual khat use; however, no systematic attempt has been made to test the hypothesis that use of khat and khat and tobacco in combination are related to sleep disturbance. Sleep disturbances are associated with dysregulations in emotional and physiological functions and can increase health risks.MethodsWe developed and used the Arabic version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
4
20
0
Order By: Relevance
“…The finding of an increased likelihood of impaired sleep in khat dependent individuals is consistent with clinical observations of khat users (10,17) as well as evidence from other investigations of habitual khat users (19,32). It is certainly possible that impaired sleep quality and/or sleep quantity may also increase the likelihood of negative affect in khat dependent individuals, therefore interacting in a synergistic manner.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The finding of an increased likelihood of impaired sleep in khat dependent individuals is consistent with clinical observations of khat users (10,17) as well as evidence from other investigations of habitual khat users (19,32). It is certainly possible that impaired sleep quality and/or sleep quantity may also increase the likelihood of negative affect in khat dependent individuals, therefore interacting in a synergistic manner.…”
Section: Discussionsupporting
confidence: 82%
“…Good PSQI test-retest reliability has been reported (31). With the permission of the PSQI authors, we translated the original English version into Arabic and then back-translated into English (32). A total score was used in the current analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The growing research evidence shows that khat is a risk factor for different cardio-vascular disorders such as hypertension, ischemic heart diseases, and stroke 3,4 . Khat is also a risk factor for poor oral health 5 , psychosis 6 , mental distress 7 , anemia 8 , poor quality of life 9 , disturbed sleep pattern [10][11][12] , and duodenal ulcer 13 .…”
Section: Introductionmentioning
confidence: 99%
“…As with mental health, adverse effects are commonly linked with prolonged or excessive use. However, the major shortcoming of this literature is that other explanations for the physical disorders have not been systematically ruled out, for example tobacco smoking which is frequently combined with khat use (15,21) and the agrochemical content in the leaves (44,45). The negative physical consequences associated with khat use include mucosal problems (46), oral lesions (47), gastric cancers and duodenal ulcers (42), hypertension (48), cardiovascular complications (49), stroke (50), sexual dysfunction (51), hepatoxicity (52) and reduced birth weight of infants born to khat-chewing mothers (53), to mention just a few.…”
Section: Physical Disordersmentioning
confidence: 99%
“…Basic research studies have found evidence of altered stress response (18), cognitive deficits (19,20) and insomnia (21) in habitual khat users. Research has shown that prolonged exposure to khat may lead to a long-lasting sensitization to the effects of other drugs (22).…”
Section: Introductionmentioning
confidence: 99%